Aislamiento, purificación y caracterización de un inhibidor de aspártico proteasa vegetal específico contra las aspártico proteasas de la broca del café (2010)
La broca del café Hypothenemus hampei es la más grave plaga de café (Coffea arabica). La digestión en el intestino medio del insecto es facilitada por aspártico proteasas. Esta es el primer registro de la caracterización de siete inhibidores de las aspártico proteasas aislados de Lupinus bogotensis (IAPLb). La secuencia amino-terminal de IAPLb1, IAPLb2, IAPLb3 IAPLb4 y IAPLb5 mostró identidad con vicilinas y δ-conglutinas de Lupinus albus, esto sugiere que estas proteínas podrían ser codificadas por una familia de genes. IAPLb4 tiene una masa molecular de 12,84 kDa, y una cadena polipeptídica con un punto isoeléctrico de 4,5. Fue estable a 70 °C y en un rango de pH, 2-11. En ensayos in vitro, IAPLb4 fue efectivo contra las aspártico proteasas de H. hampei con una IC50 de 2,9 μg. IAPLb4 inhibió pepsina con una relación estequiométrica de 1:1 y el Ki fue de 3,1 μM. Su secuencia amino-terminal mostró 76% de identidad con vicilina y β-conglutinas. Esto indica que IAPLb4 puede actuar como proteína de reserva en la semilla y ser una herramienta promisoria para la producción de café resistente a H. hampei. El gen que codifica el inhibidor IAPLb4 corresponde a un único marco de lectura abierto de 354 nucleótidos que codifican para un polipéptido de 117 aminoácidos y su secuencia genómica no tiene intrones. IAPLb6 e IAPLb7 están constituidos por una cadena polipeptídica con una masa molecular de 12,86 y 16,91 kDa, respectivamente, y su secuencia amino-terminal tiene identidad con la δ-conglutina de L. albus. / Abstract. The coffee berry borer, Hypothenemus hampei (Ferrari), is the most devastating pest affecting coffee crops (Coffea arabica) not only in Colombia but worldwide. This insect feeds and grows on the coffee bean endosperm, needing proteolytic enzymes for digestion. The presence of aspartic proteolytic activity in the mid-gut of H. hampei larvae and adults offers an alternative for insect control. This work describes the identification, purification, and characterization of the first inhibitor of aspartic proteases of H. hampei, as well as the cloning of gene encoding an inhibitor of aspartic proteases of this beetle. Extracts of seeds of Lupinus bogotensis, Brachiaria humidicola, Amaranthus hypochondriacus, Phaseolus acutifolius, Phaseolus coccineus, Hyptis suaveolens, Centrosema pubescens, and Trifolium repens were evaluated to identify aspartic protease inhibitors. The greatest inhibitory activity was found in the L. bogotensis extract. Protease inhibitors isolated from L. bogotensis seeds were purified by pigment elimination, precipitation with ammonium sulfate, anionic exchange chromatography, and protein gel elution. Aspartic protease inhibitors of L. bogotensis (LbAPI) were designated as LbAPI1, LbAPI2, LbAPI3, LbAPI4, LbAPI5, LbAPI6, and LbAPI7. Among these, LbAPI1, LbAPI2, LbAPI3, LbAPI4, and LbAPI5 have a single polypeptide chain and its amino-terminal sequence showed features similar to the vicilins and β-conglutins of L. albus, suggesting that these proteins could be coded by a family of genes. LbAPI6 is composed by a polypeptide chain with a molecular mass of 12,86 kDa, and LbAPI7 by a polypeptide chain with a molecular mass of 16,91 kDa. The amino-terminal sequence of LbAPI6 and LbAPI7 has identity with the β-conglutin of L. albus. LbAPI4 triggered the greatest inhibition of aspartic proteases of H. hampei; this inhibitor has a molecular mass of 12,84 kDa determined by Maldi-Tof; LbAPI4 is composed by a single polypeptide chain with an isoelectric point of 4,5. Its aminoterminal sequence is similar with seed storage proteins, vicilins, and β-conglutins of L. albus and L. angustifolius. The identity of LbAPI4 with vicilins of L. albus suggests that these storage proteins may play a defense role. LbAPI4 maintained 100% inhibitory activity at 70°C, but was unstable at 100°C. It was also stable in a broad range of pH from 2 to 11 at 30°C. In in vitro tests, LbAPI4 was highly effective against the aspartic proteases of H. hampei, with a half maximal inhibitory concentration (CI50) of 2.9 μg. LbAPI4 inhibits pepsin at a stoichiometric ratio of 1:1 and an inhibition constant (Ki) of 3.1 μm. The gene that codes the LbAPI4 inhibitor corresponds to a sole open reading frame of 354 nucleotides that code for a polypeptide of 117 amino acids. Just like other protease inhibitors, its genomic sequence does not have introns. This sequence has a signal peptide with a cleavage site between positions AYG-EK. This sequence is probably lost during the maturation of the native inhibitor and accounts for 32% of the translated protein. The gene that codes LbAPI4 could be a promising tool to produce coffee plants resistant to H. hampei. This work confirmed the existence of protease inhibitors in Lupinus spp. seeds, contradicting former reports of the lack of protease inhibitory activity in L. albus and Lupinus luteus.